Time to Recovery and Its Predictors in Patients with Traumatic Brain Injury Who Underwent Urgent Neurosurgical Intervention at ALERT Trauma Center, Ethiopia - Woldesenbet EB; Belachew FK; Gezae KE; Meles GG; Ali FY; Firissa YB; Kyaruzi VM (Open Access Surgery, 2024)
Ermiyas Belay Woldesenbet,1,2 Fitsum Kifle Belachew,2,3 Kebede Embaye Gezae,4 Gebrekiros Gebremichael Meles,4 Fedila Yassin Ali,1 Yared Boru Firissa,5 Victor Meza Kyaruzi6,7 1Department of Public Health, College of Health Science, Wolkite University, Wolkite, Ethiopia; 2Debre Berhan University Asrat Woldyes Health Sciences Campus, Network for Perioperative and Critical Care, Addis Ababa, Ethiopia; 3Division of Global Surgery, University of Cape Town, Cape Town, South Africa; 4Department of Biostatistics, School of Public Health, College of Health Sciences, Mekelle University, Mekelle, Tigray, Ethiopia; 5Emergency Medicine and Critical Care Department, ALERT Hospital, Addis Ababa, Ethiopia; 6Research Department, Winners Foundation, Yaounde, Cameroon; 7Department of Surgery, School of Medicine, Muhimbili University of Health Sciences, Dar Es Salaam, TanzaniaCorrespondence: Ermiyas Belay Woldesenbet, Email Ermiyasbelay03@gmail.comPurpose: This study aimed to assess and compare the in-hospital recovery times between two groups: those exposed to early intervention and those with late intervention in a cohort of Traumatic Brain Injury (TBI) patients requiring urgent neurosurgical intervention in ALERT Trauma Center in Addis Ababa, Ethiopia.Methods: The study was conducted over seven consecutive months, from March 14, 2020, to October 13, 2020. Patients were consecutively recruited from the emergency department until the final sample size was fulfilled. The recovery time between the early and late surgery groups was compared using the Log rank test. The Cox proportional hazard model was used to analyze the event data, with the assumption of proportional hazards being checked. The measure of effect was reported using the adjusted hazard ratio, and a stepwise approach was used to build the final model.Results: A total of 117 TBI patients undergoing urgent neurosurgical intervention were observed and the median survival time for the early surgery group was 4.1 days, and for the late surgery group, it was 6.4 days, with no statistically significant difference (CHR: 0.73; 95% CI; 0.47– 1.11). On the other hand, severe TBI grade emerged as a significant independent predictor, indicating an 86% lower rate of recovery compared to mild TBI cases. Additionally, higher diastolic blood pressure within the range of 50 to 100 was associated with a 24% increased rate of recovery.Conclusion: This study identified factors influencing recovery outcomes and predictors of prolonged recovery, specifically severe TBI grade and lower diastolic blood pressure. The results emphasize the importance of timely intervention and provide specific considerations for optimizing patient outcomes in TBI cases and guiding further research in the area.Keywords: Glasgow outcome score, severe, TBI, neurosurgery